Feasibility analysis and contribution of beekeeping to the welfare of beekeepers in Gunung Megang, Muara Enim Regency, South Sumatra Province, Indonesia - Beni Rahmad; Nurhayati Damiri; Zazili Hanafiah; Dessy Adriani (Dinasti Publisher, 2024)
The purpose of this study was to obtain data on costs incurred from the production process, and data on farmer income from beekeping. The total revenue data is then used to analyze the feasibility of beekeeping and its contribution to increasing farmers welfare. The research was carried out using a survey with a quantitative method. Respondents were determined by purposive sampling, the members of Sari Puspa Farmers Group domiciled in Sumaja Makmur Village, Gunung Megang, Muara Enim Regency, totaling 20 peoples. Respondents are farmers who also work as beekeepers in their rubber and oil palm plantations. From the results of research on the cash flow of each beekeeper during 2022, a total revenue (TR) of IDR 152,600,000,- and the total cost of production (TC) is IDR 21,900,000.-. So that overall a total income of IDR 130,700,000,- with an average profit of IDR 6,535,000,- per year. Meanwhile, from farming activity, which is the main job of beekeepers, the average annual income per hectare of arable land is IDR 38,400,000,- so that the total income of the farmer's household is IDR 44,935,000,- per year. Income from the beekeping contributes 14.5%, and is included in the low category. The initial investment value based on financial feasibility analysis is IDR 11.153.600,- While the income for 1 harvest period is IDR. 6,535,000,-. So based on these data the BEP of production is 102 Kg. The bekepers will break even if production reaches or exceeds 102 Kg. Meanwhile, at a BI rate of 5.75%, NPV of IDR 13,564,82,- is obtained, an IRR value of 55%, B/C ratio value of 1.61 and a Payback period of 1 year 8 months and 8 days. Based on the analysis indicators, the beekeeping at Farmer Group of Sari Puspa is in the feasible category.